Axial compressive performance of RAC-encased RACFST composite columns. (1st May 2020) - Cai, Min; Ke, Xiaojun; Su, Yisheng
Highlights: Axial compressive behavior of RAC-encased RACFST composite columns was investigated. The whole load-deformation curves and mechanical performance of specimens were obtained. The calculation methods of their bearing capacity are presented and compared. Abstract: A new type of composite column, recycled aggregate concrete (RAC)-encased recycled aggregate concrete-filled steel tube (RACFST) composite columns, promotes the RAC extensive utilization considering synergistic effect between the RAC and the steel tube, which is an attempt to develop environmentally sustainable concrete in high-rise buildings. In this paper, experimental research investigated the axial compressive behavior of RAC-encased RACFST composite columns. Twenty 1:3-scaled specimens were fabricated to test until failure under axial compressive loading. The main variable parameters affecting the behaviour of specimens were recycled coarse aggregate replacement ratio (range from 0% to 100% with 10% increase), stirrup spacing ( s  = 50 mm, 70 mm, 100 mm, 120 mm), diameter of steel tube ( D  = 89 mm, 114 mm), concrete strength grade (RC40, RC60) and longitudinal reinforcement ratio (4 12, 8 12). The failure modes, the whole load-deformation curves and the mechanical performance of specimens were also obtained based on static loading experiments and theoretical analysis. It was found that RAC-encased RACFST composite columns, which were subjected to identical axial loads, exhibited more favorable bearing capacity and deformation than those of a comparative reinforced recycled aggregate concrete columns (RACC). The replacement ratio of RCA had a slight effect on the mechanical performance of RAC-encased RACFST composite columns, the optimal substitution ratio of RCA was 50–60%. Based on the previous theory of superposition, the concrete cover is considered, and a calculation formula with double reduction coefficients of the axial load-bearing capacity of composite columns is proposed. Compared to the simplified superimposition method and the Chinese code Technical specification for steel tube-reinforced concrete column structure (CECS188:2005), the calculated results of axial compression bearing capacity by the proposed formula are in more agreement with the experimental values, with errors no greater than 15%.